1. The problem statement, all variables and given/known data (2^x - 2^-x)/3=4 2. Relevant equations Using log or exponential rules 3. The attempt at a solution First multiply both sides by 3 so 2^x-2^-x=12 I thought I could take the log of both sides then condense the log, but that is not right. I also attempted to rewrite as 2^x - 1/(2^x) = 12 but I could nowhere with that. I also attempted to do (2 - 2^-1)^x = 12 (2-1/2)^x = 12 (3/2)^x = 12 log(3/2)^x = log 12 x(log 3/2) = log 12 x= log 12/log 3/2 = 6.128 But that is not the right answer it is supposed to be 3.595 . Where did I go wrong?